A 3D printed titanium alloy powder and its production process

By using hydrogen mixed with argon and nano-ytterbium hexaboride and nano-erbium dopants in the titanium alloy gas atomization process, the problems of complex traditional titanium alloy processing technology and high cost of 3D printing titanium alloys are solved, and high yields are achieved , 3D printing titanium alloy powder with low oxygen increment and excellent mechanical properties.

CN118455528BActive Publication Date: 2025-01-21JIANGSU VILORY ADVANCED MATERIALS TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410787402.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-18
Publication Date
2025-01-21
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

The traditional titanium alloy has complex processing technology, low material utilization and high cost, and the particle size of the titanium alloy ball powder prepared by electrode induction atomization method is low in yields below 45 microns, resulting in a high cost of 3D printing of titanium alloys.

Method used

Hydrogen mixed with argon is used as the atomizing gas. The Ti-6Al-4V titanium alloy is doped with nano-ytterbium hexaboride and nano-erbium in the electrode induction gas atomization method. The mixture containing metal dopants is sprayed through the nozzle. Argon gas crushes the titanium alloy melt to prepare low-oxygen ultra-fine 3D printing titanium alloy powder.

Benefits of technology

It improves the yield and quality of low-oxygen ultra-fine titanium alloy powder. The particle size is between 5-80 μm. The powder rate of particle size less than 53 μm can reach 56%. It also significantly reduces the oxygen increase of 3D printing titanium alloy powder. quantity, improving the mechanical properties of 3D printed parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118455528B_ABST
    Figure CN118455528B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of titanium alloy production, and specifically discloses a 3D printed titanium alloy powder and its production process. A production process for 3D printed titanium alloy powder, using hydrogen mixed with argon as atomizing gas, using hydrogen to weaken the surface tension and viscosity of the titanium alloy melt, making it easier to disperse into finer droplets, and obtaining a powder with a smaller particle size, while also reducing the amount of oxygen added to the atomized powder; by adding a certain proportion of nano ytterbium hexaboride and nano erbium, the nano ytterbium hexaboride and nano erbium are bonded to the surface of the titanium alloy during the atomization process of the titanium alloy, thereby realizing the metal doping modification of the titanium alloy. The 3D printed titanium alloy powder prepared by the present application has the characteristics of low oxygen increment and high fine powder rate, and the 3D printed parts prepared using the powder have good mechanical properties such as hardness, tensile yield strength, tensile strength and elongation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of titanium alloy production, and more specifically, it relates to a 3D printed titanium alloy powder and a production process thereof. Background Art

[0002] Titanium alloys have the advantages of high specific strength, good corrosion resistance and good biocompatibility, and are widely used in aviation, aerospace, shipbuilding, chemical industry and biomedicine. However, due to its low thermal conductivity, low elastic modulus and active chemical properties, the traditional manufacturing and processing of titanium alloys is complicated, with low material utilization and high cost.

[0003] Applying 3D printing technology to titanium alloy processing can effectively circumvent the problem of difficult traditional machine parts processing. At the same time, combining 3D printing technology with topological design, by using the designed data model and high-energy heating device to sinter titanium alloy ball powder layer by layer to make components of the expected shape, can achieve structural weight reduction, thereby improving material utilization, greatly reducing the manufacturing cost of titanium alloy parts, and promoting the application of titanium alloy products in a wider range of fields such as aerospace, biomedicine, etc.

[0004] There are many methods for preparing spherical titanium alloy powder, such as molten salt electrolysis, hydrogenation and dehydrogenation, gas atomization, rotating electrode method and plasma spheroidization method. The former two technologies are immature and are mostly still in the experimental stage. The latter three can mass produce spherical titanium alloy powder, but it is difficult to obtain fine powder below 45μm using rotating electrode and plasma spheroidization. The low-oxygen ultrafine titanium alloy powder required for high-end 3D printing is mainly prepared by gas atomization.

[0005] The atomization method is divided into inert gas atomization, ultrasonic atomization and electrode induction atomization. Among them, the electrode induction atomization method is the main method for the production of titanium alloy ball powder. Its technical principle is: using high-speed and high-pressure argon gas flow to impact the titanium alloy melt. The high-speed gas flow can overcome the surface tension of the titanium alloy melt, and the atomized melt droplets are formed into fine metal droplets. The fine metal droplets cool and solidify under the action of the tension to form spherical powder. Compared with the first two, the electrode induction atomization method has low production cost and high production efficiency. However, the particle size of the titanium alloy ball powder prepared by the electrode induction atomization method can only reach about 30% below 45 microns, which leads to a higher price for ultrafine titanium alloy ball powder and a higher cost for 3D printing of titanium alloy. Summary of the invention

[0006] In order to further improve the yield and quality of low-oxygen ultrafine titanium alloy powder, the present application provides a 3D printed titanium alloy powder and a production process thereof.

[0007] In the first aspect, the present application provides a production process for 3D printing titanium alloy powder, which adopts the following technical solution:

[0008] A production process for 3D printing titanium alloy powder, comprising the following steps: S1, pretreatment: degreasing and deoiling the original titanium alloy rod; S2, feeding: placing the titanium alloy rod as an electrode in the induction coil of an electrode induction gas atomization device, and then evacuating the cavity of the electrode induction gas atomization device; S3, melting: increasing the smelting power to 35-40KW, and the titanium alloy rod is melted in the smelting zone; S4, powder adding: adding a metal dopant to the mixed argon gas through an argon gas inlet pipe; S5, atomization: when the titanium alloy rod is melted into a liquid flow and falls, it is broken into fine liquid by the mixed argon gas containing the metal dopant sprayed through the nozzle of the atomizing spray disk, and the fine droplets are quickly cooled and solidified into powder, i.e., atomized powder; S6, screening: screening the atomized powder in a protective atmosphere with an argon gas pressure of 1.1 atmospheres to obtain 3D printing titanium alloy powder; the mixed argon gas consists of argon gas and hydrogen.

[0009] By adopting the above technical scheme, hydrogen mixed with argon is used as the atomizing gas, and the Ti-6Al-4V titanium alloy is doped with nano-ytterbium hexaboride and nano-erbium in a certain proportion during the atomization process, a low-oxygen ultrafine 3D printing titanium alloy powder is prepared, and the particle size is between 5-80μm, among which the powder rate with a particle size less than 53 microns can reach 56%, and the 3D printed parts prepared in this way have good mechanical properties.

[0010] Preferably, the nozzle angle is 30-45°.

[0011] By adopting the above technical solution, the nozzle will not spray back within this angle range.

[0012] Preferably, the vacuum degree in S2 is ≤0.01Pa.

[0013] By adopting the above technical solution, vacuum is drawn to reduce the influence of oxygen as much as possible.

[0014] Preferably, the titanium alloy bar material descending rate is 35-40 mm / min.

[0015] By adopting the above technical solution, the particle size of the atomized powder obtained at the descending speed is smaller.

[0016] Preferably, the pressure of the mixed argon gas containing the metal dopant ejected from the nozzle is 2-4 MPa, and the flow rate of the mixed argon gas is set to 500-600 m / s. 3 / h.

[0017] By adopting the above technical solution, the particle size of the atomized powder obtained under the airflow is smaller.

[0018] Preferably, the volume percentage of hydrogen in the mixed argon gas is: (0.1-0.5)%.

[0019] By adopting the above technical solution, hydrogen at this ratio can effectively reduce the surface tension and viscosity of the crushed titanium alloy melt and reduce the oxygen increment of the obtained atomized powder.

[0020] Preferably, the mass ratio of the nano-ytterbium hexaboride to the nano-erbium is (1.2-1.5): (2.5-3.0).

[0021] By adopting the above technical solution, the 3D printed titanium alloy powder obtained under this ratio has excellent mechanical properties.

[0022] Preferably, the speed of adding the metal dopant is 0.5-1.2 mg / s, and the particle size of the metal dopant is 50-100 nm.

[0023] By adopting the above technical solution, the metal dopant can be adhered to the surface of the titanium alloy to a greater extent during the atomization process of the titanium alloy.

[0024] In a second aspect, the present application provides a 3D printed titanium alloy powder prepared by the above-mentioned production process.

[0025] In summary, this application has the following beneficial effects:

[0026] 1. This application uses hydrogen mixed with argon as atomizing gas, and dopes Ti-6Al-4V titanium alloy with nano-ytterbium hexaboride and nano-erbium in a certain ratio to prepare low-oxygen ultrafine 3D printing titanium alloy powder with a particle size between 5-80 μm, among which the powder rate with a particle size less than 53 microns can reach 56%.

[0027] 2. In the present application, hydrogen mixed with argon is preferably used as the atomizing gas. Hydrogen is used to weaken the surface tension and viscosity of the titanium alloy melt, making it easier to disperse into finer droplets and obtain powders with smaller particle sizes. At the same time, it also plays a role in reducing the amount of oxygen added to the atomized powder. By adding a certain proportion of nano-ytterbium hexaboride and nano-erbium, the nano-ytterbium hexaboride and nano-erbium are bonded to the surface of the titanium alloy during the atomization process of the titanium alloy, thereby improving the mechanical properties of its 3D printed parts.

[0028] 3. The 3D printed titanium alloy powder prepared by the production method of the present application has low oxygen increment and high fine powder rate, and the 3D printed parts prepared by this method have good mechanical properties such as hardness, tensile yield strength, tensile strength and elongation. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 : Scanning electron microscope morphology of the atomized powder prepared in Example 1 of the present application.

[0030] Figure 2 : Cumulative distribution curve of particle size of atomized powders of Example 2 of the present application and Comparative Examples 1, 2, 3, and 5. DETAILED DESCRIPTION

[0031] The present application is further described in detail below with reference to the embodiments.

[0032] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0033] Example

[0034] Example 1

[0035] A production process for 3D printing titanium alloy powder, comprising the following steps:

[0036] S1, pretreatment: degreasing and deoiling the original titanium alloy bar; the material of the original titanium alloy bar is Ti-6Al-4V;

[0037] S2, adding material: placing the treated titanium alloy rod as an electrode in the induction coil of the electrode induction atomization equipment, and then evacuating the cavity of the electrode induction atomization equipment to a vacuum degree of ≤0.01Pa;

[0038] S3, melting material: the melting power is increased to 35KW, the titanium alloy bar is melted in the melting zone, and the descending rate of the titanium alloy bar is 35mm / min;

[0039] S4, adding powder: adding a metal dopant into the mixed argon gas through the argon gas inlet pipe; the metal dopant is a mixture of nano ytterbium hexaboride and nano erbium in a mass ratio of 1.2:2.5, the particle size of the metal dopant is 50nm, and the adding speed of the metal dopant is 0.5mg / s.

[0040] S5, atomization: When the titanium alloy bar melts into a liquid flow and falls, it is broken into fine liquid by the mixed argon gas containing metal dopants sprayed through the nozzle of the atomizing spray plate. The fine liquid droplets are quickly cooled and solidified into powder, i.e., atomized powder. The mixed argon gas flow pressure containing metal dopants sprayed through the nozzle is 2MPa, and the mixed argon gas flow rate is set to 550m 3 / h, the volume percentage of hydrogen in the mixed argon is: 0.1%; the angle of the nozzle is 45°.

[0041] S6, sieving: sieving the atomized powder in a protective atmosphere of argon gas at 1.1 atmospheres to obtain 3D printing titanium alloy powder.

[0042] The morphology of the atomized powder prepared in Example 1 was characterized by scanning electron microscopy. Figure 1 As shown. Figure 1 It can be seen that the particle size of the atomized powder is relatively small, with most of the particle sizes being around 50 μm, and metal dopants are bonded to the surface of the atomized powder.

[0043] The oxygen increment of the obtained 3D printed titanium alloy powder was 78ppm.

[0044] Example 2

[0045] A production process for 3D printing titanium alloy powder, comprising the following steps:

[0046] S1, pretreatment: degreasing and deoiling the original titanium alloy bar; the material of the original titanium alloy bar is Ti-6Al-4V;

[0047] S2, adding material: placing the treated titanium alloy rod as an electrode in the induction coil of the electrode induction atomization equipment, and then evacuating the cavity of the electrode induction atomization equipment to a vacuum degree of ≤0.01Pa;

[0048] S3, melt: increase the melting power to 38KW, the titanium alloy bar is melted in the melting zone, and the descending rate of the titanium alloy bar is 37mm / min;

[0049] S4, adding powder: adding a metal dopant into the mixed argon gas through the argon gas inlet pipe; the metal dopant is a mixture of nano ytterbium hexaboride and nano erbium in a mass ratio of 1.3:2.8, the particle size of the metal dopant is 80nm, and the adding speed of the metal dopant is 1.0mg / s.

[0050] S5, atomization: When the titanium alloy bar melts into a liquid flow and falls, it is broken into fine liquid by the mixed argon gas containing metal dopants sprayed through the nozzle of the atomizing spray plate. The fine liquid droplets are quickly cooled and solidified into powder, i.e., atomized powder; the mixed argon gas flow pressure containing metal dopants sprayed through the nozzle is 3MPa, and the mixed argon gas flow rate is set to 550m 3 / h, the volume percentage of hydrogen in the mixed argon is: 0.3%, and the angle of the nozzle is 40°.

[0051] S6, sieving: sieving the atomized powder in a protective atmosphere of argon gas at 1.1 atmospheres to obtain 3D printing titanium alloy powder.

[0052] A powder feeder is connected to the argon gas inlet pipe of the electrode induction gas atomization equipment, and the powder feeder is used to add metal dopants to the argon gas inlet pipe of the electrode induction gas atomization equipment. The atomization spray disc of the electrode induction gas atomization equipment is an integrated full design. In order to prevent the metal dopants added to the mixed argon gas from damaging the sealing structure of the spray disc, the guide pipe and the upper pressure plate of the integrated spray disc are also integrally formed.

[0053] The oxygen increment of the obtained 3D printed titanium alloy powder was 82ppm.

[0054] Example 3

[0055] A production process for 3D printing titanium alloy powder, comprising the following steps:

[0056] S1, pretreatment: degreasing and deoiling the original titanium alloy bar; the material of the original titanium alloy bar is Ti-6Al-4V;

[0057] S2, adding material: placing the treated titanium alloy rod as an electrode in the induction coil of the electrode induction atomization equipment, and then evacuating the cavity of the electrode induction atomization equipment to a vacuum degree of ≤0.01Pa;

[0058] S3, melting material: the melting power is increased to 40KW, the titanium alloy bar is melted in the melting zone, and the descending rate of the titanium alloy bar is 40mm / min;

[0059] S4, adding powder: adding a metal dopant into the mixed argon gas through an argon gas inlet pipe; the metal dopant is a mixture of nano ytterbium hexaboride and nano erbium in a mass ratio of 1.5:3.0, the particle size of the metal dopant is 100 nm, and the adding speed of the metal dopant is 1.2 mg / s.

[0060] S5, atomization: When the titanium alloy bar melts into a liquid flow and falls, it is broken into fine liquid by the mixed argon gas containing metal dopants sprayed through the nozzle of the atomizing spray plate. The fine liquid droplets are quickly cooled and solidified into powder, i.e., atomized powder. The mixed argon gas flow pressure containing metal dopants sprayed through the nozzle is 4MPa, and the mixed argon gas flow rate is set to 600m 3 / h, the volume percentage of hydrogen in the mixed argon is: 0.5%; the angle of the nozzle is 30°.

[0061] S6, sieving: sieving the atomized powder in a protective atmosphere of argon gas at 1.1 atmospheres to obtain 3D printing titanium alloy powder.

[0062] The oxygen increment of the obtained 3D printed titanium alloy powder was 85ppm.

[0063] Comparative Example

[0064] Comparative Example 1

[0065] The same as Example 2, except that the "mixed argon gas" was replaced with "argon gas", that is, no hydrogen was added to the atomizing gas. The oxygen increment of the obtained 3D printing titanium alloy powder was 216 ppm.

[0066] Comparative Example 2

[0067] The same as Example 2, except that no metal dopant was added. The oxygen increment of the obtained 3D printing titanium alloy powder was 93 ppm.

[0068] Comparative Example 3

[0069] The same as Example 2, except that nano ytterbium hexaboride is not added to the metal dopant.

[0070] Comparative Example 4

[0071] The same as Example 2, except that nano-erbium is not added to the metal dopant.

[0072] Comparative Example 5

[0073] The same as Example 2, except that the particle size of the dopant is 10 μm.

[0074] Comparative Example 6

[0075] The same as Example 2, except that no metal dopant was added and the atomizing gas was only argon. The oxygen increment of the obtained 3D printed titanium alloy powder was 235 ppm.

[0076] Combining Examples 1-3 and Comparative Examples 1, 2 and 6, it can be seen that mixing an appropriate amount of hydrogen into the traditional atomizing gas argon can reduce the oxygen increment of 3D printed titanium alloy powder, while the addition of metal dopants has little effect on this.

[0077] Performance testing

[0078] (1) The particle size of the atomized powders of Example 2 and Comparative Examples 1, 2, 3, and 5 after atomization was measured, and the cumulative distribution curve of the particle size of the atomized powders was obtained by statistics, as shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the particle size of the atomized powder prepared in Example 2 of the present application is between 5-80 μm, among which the yield of powder with a particle size less than 53 μm is 56%. Combined with Comparative Example 1, it can be seen that mixing an appropriate amount of hydrogen into the traditional atomizing gas argon can obtain a smaller atomized powder particle size, and the particle size distribution range becomes narrower; combined with Comparative Examples 2 and 3, the type of metal dopant mainly affects the particle size of the atomized powder; combined with Comparative Example 5, the particle size of the metal dopant has a greater impact on the particle size distribution range of the atomized powder.

[0079] (2) The 3D printed titanium alloy powders prepared in Examples 1-3 and Comparative Examples 1-5 were printed into a molding substrate using a Radium Laser LiM-X260A printer. The specific process parameters were: powder feeding gas flow rate 5 L / min, powder feeding speed 6 r / min, current 55 A, frequency 50 Hz, pulse width 1.2 ms, and Z-axis single-layer travel 0.4 mm. The mechanical properties of the printed parts were tested, and the results are shown in Table 1:

[0080] Table 1. Performance test

[0081]

[0082] It can be seen from Table 1 that the hardness of the molded substrate printed by the 3D printed titanium alloy powder prepared by Examples 1-3 of the present application is as high as 561HV, the tensile yield strength reaches 1796MPa, the maximum tensile strength is 1780-1796MPa, and the elongation is up to 10.36, among which Example 2 has the best comprehensive performance; combined with Comparative Examples 1 and 6, it can be seen that mixing 0.1-0.5% hydrogen into argon helps to improve the comprehensive performance of the molded substrate printed by 3D printed titanium alloy powder; combined with Comparative Example 2, it can be seen that the addition of metal dopants can further improve the various properties of the molded substrate printed by 3D printed titanium alloy powder; combined with Comparative Example 3, it can be seen that the addition of nano-ytterbium hexaboride has a greater effect on its tensile yield strength and tensile strength; combined with Comparative Example 4, it can be seen that the addition of nano-erbium has a greater effect on its hardness and elongation; combined with Comparative Example 5, it can be seen that metal dopants with smaller particle sizes are more conducive to improving its various properties.

[0083] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.

Claims

1. A production process for 3D printing titanium alloy powder, characterized in that: The following steps are involved: S1, pretreatment: degreasing and deoiling the original titanium alloy rod; S2, feeding: placing the titanium alloy rod as an electrode in the induction coil of the electrode induction gas atomization equipment, and then evacuating the cavity of the electrode induction gas atomization equipment; S3, melting: increasing the smelting power to 35-40KW, the titanium alloy rod is melted in the smelting area; S4, powder adding: adding metal dopants to the mixed argon gas through the argon gas inlet pipe; S5, atomization: when the titanium alloy rod is melted into a liquid flow and falls, it is broken into fine liquid by the mixed argon gas containing metal dopants sprayed through the nozzle of the atomizing spray plate. The droplets are rapidly cooled and solidified into powder, i.e., atomized powder; S6, screening: screening the atomized powder in a protective atmosphere of argon gas at 1.1 atmospheres to obtain 3D printed titanium alloy powder; the mixed argon gas consists of argon gas and hydrogen gas, and the volume percentage of hydrogen gas in the mixed argon gas is: (0.1-0.5)%; the metal dopant is a mixture of nano ytterbium hexaboride and nano erbium, the mass ratio of nano ytterbium hexaboride and nano erbium is (1.2-1.5):(2.5-3.0), the particle size of the metal dopant is 50-100nm, and the addition rate of the metal dopant is 0.5-1.2mg / s.

2. A production process for 3D printing titanium alloy powder according to claim 1, characterized in that: The nozzle angle is 30-45°.

3. A production process for 3D printing titanium alloy powder according to claim 2, characterized in that: The vacuum degree in S2 is ≤0.01Pa.

4. A production process for 3D printing titanium alloy powder according to claim 3, characterized in that: The titanium alloy bar descending rate is 35-40mm / min.

5. A production process for 3D printing titanium alloy powder according to claim 4, characterized in that: The mixed argon gas flow pressure containing metal dopants ejected from the nozzle is 2-4 MPa, and the mixed argon gas flow rate is set to 500-600 m 3 / h.

6. A 3D printed titanium alloy powder, characterized in that: Prepared by the production process described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Low-oxygen fine metal powder for 3D printing and preparation method of low-oxygen fine metal powder

    CN105458246A

  • Preparation method of spherical metal based nano ceramic composite material used for three-dimensional printing and product

    CN109014179A

  • Rare earth reinforced titanium-based composite material and preparation method thereof

    CN115889791A

  • High-plasticity Ti-Nb-based alloy ultrafine powder and forming process thereof

    CN116475405A